Using ichthyotoxic plants as bioinsecticide: A literature review - J. N. ANDRADE; E. M. COSTA NETO; H. BRANDÃO (Universidade Estadual Paulista, 2015)
ABSTRACTSome ichthyotoxic plants are study object aiming to discover promising substances in the field of Biotechnology, in search of plant extracts which can be used or even transformed into natural insecticides. This paper presents a bibliographical survey in order to check the traditional use of ichthyotoxic plants as bioinsecticide. Among the plants identified as ichthyotoxic, the most cited in traditional use are those from the genera Derris, Serjania, Lonchocarpus, Magonia, and Tephrosia. The survey suggests that ichthyotoxic plant extracts can contain classes of chemical compounds such as isoflavonoids and tannins with a bioinsecticidal effect and, thus, they can be used in Biotechnology, contributing to reduce the use of synthetic insecticides that present a high toxicity level.